ANALISIS PENGARUH RETURN ON ASSET, DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arisanti B11108071, Wenty Ria (Jurnal Manajemen Update, 2014)
Investment is an activity that places funds in one or more assets in certain period in order to obtain income or an increase in value of initial investment which aims to maximize return in certain period of time accepted by every investor. The presence of stock market in Indonesia affects investors to invest their money in food and drinks industries. Rapid development of these industries is followed by high demand for food needs; as a result consumer demand increases and needs more funds from external sources. This can be gained from stock market. This research aims to analyze influence of return on asset, debt to equity ratio on return stock in food and drinks companies in Indonesia stock Exchange from 2007 to 2011. The population of this study was eleven food and drinks companies in Indonesia stock Exchange. The data was from PT Indonesia stock Exchange between 2007 and 2011. The data analysis used multiple linear regressions to get overall picture about relationship among the variables. The results of this study indicate that the variabel return on asset positively and significantly related to stock returns, debt to equity ratio and significantly positively related to stock return. Keywords: Return on Asset, Debt to Equity Ratio and Return Stock.